Influence of Injection Pressure on the Dual-Fuel Mode in CI Engines Fueled with Blends of Ethanol and Tamanu Biodiesel. (28th November 2022) - Parthasarathy, M.; Elumalai, P. V.; Murunachippan, M.; Senthilkumar, P. B.; Shaik, Saboor; Sharifpur, Mohsen; Khalilpoor, Nima
Abstract : The acceleration of global warming is primarily attributable to nonrenewable energy sources such as conventional fossil fuels. The primary source of energy for the automobile sector is petroleum products. Petroleum fuel is depleting daily, and its use produces a significant amount of greenhouse emissions. Biofuels would be a viable alternative to petroleum fuels, but a redesign of the engine would be required for complete substitution. The use of CNG in SI engines is not new, but it has not yet been implemented in CI engines. This is due to the fuel having a greater octane rating. The sole use of CNG in a CI engine results in knocking and excessive vibration. This study utilizes CNG under dual-fuel conditions when delivered through the intake manifold. In a dual-fuel mode, compressed natural gas (CNG) is utilized as the secondary fuel and a blend of 90% tamanu methyl ester and 10% ethanol (TMEE10) is used as the primary fuel. The injection pressure (IP) of the primary fuel changes between 200 and 240 bar, while the CNG induction rate is kept constant at 0.17 kg/h. The main combustion process is governed by the injection pressure of the pilot fuel. It could be affecting factors such as the vaporization characteristics of the fuel, the homogeneity of the mixture, and the ignition delay. Originally, tamanu methyl ester (TME) and diesel were used as base fuels in the investigation. As a result of its inherent oxygen content, TME emits more NOx than diesel. The addition of 10% ethanol to TME (TMEE10) marginally reduces NOx emissions in a CI mode because of its high latent heat of vaporization characteristics. Under peak load conditions, NOx emissions of TMEE10 are 6.2% lower than those of neat TME in the CI mode. Furthermore, the experiment was conducted using TMEE10 as the primary fuel and CNG as the secondary fuel. In the dual-fuel mode, the TMEE10 blend showed higher combustion, resulting in an increase in performance and a significant decrease in emission characteristics. As a result of the CNG's high-energy value and rapid burning rate, the brake thermal efficiency (BTE) of TMEE10 improves to 29.09% compared to 27.09% for neat TME. In the dual-fuel mode of TMEE10 with 20.2% CNG energy sharing, the greatest reduction in fuel consumption was 2.9%. TMEE10 with CNG induction emits 7.8%, 12.5%, and 15.5% less HC, CO, and smoke, respectively, than TME operation.